Fiscal Impulses and their Fiscal Impact - Chand, Sheetal (IMF Working Papers; Working Paper, 1992)
Fiscal impulse measures are used in the WEO and elsewhere to indicate the changing impact of the budget on the economy. Such measures are intended to provide more accurate indications of whether the budget is becoming more or less expansionary than would just observing moments in the actual budget balance. However, they have been criticized for lacking an analytical rationale. This paper uses a simple framework to show that the fiscal impulse measure can be analytically derived. While this removes one source of criticism, the measure, nevertheless, should be used carefully when making inferences of fiscal impact.